ProBioQuest: a database and semantic analysis engine for literature, clinical trials and patents related to probiotics. (15th July 2022) - Chan, Po Lam; Lauw, Susana; Ma, Ka Lee; Kei, Nelson; Ma, Ka Leong; Wong, Yiu On; Lam, Ho Yan; Ting, Yee Yung; Yau, Tsz Kwan; Nong, Wenyan; Huang, Dandan; Xie, Yichun; et al.
Abstract: The use of probiotics to improve health via the modulation of gut microbiota has gained wide attention. The growing volume of investigations of probiotic microorganisms and commercialized probiotic products has created the need for a database to organize the health-promoting functions driven by probiotics reported in academic articles, clinical trials and patents. We constructed ProBioQuest to collect up-to-date literature related to probiotics from PubMed.gov, ClinicalTrials.gov and PatentsView. More than 2.8 million articles have been collected. Automated information technology-assisted procedures enabled us to collect the data continuously, providing the most up-to-date information. Statistical functions and semantic analyses are provided on the website as an advanced search engine, which contributes to the semantic tool of this database for information search and analyses. The semantic analytical output provides categorized search results and functions to enhance further analysis. A keyword bank is included which can display multiple tables of contents. Users can select keywords from different displayed categories to achieve easily filtered searches. Additional information on the searched items can be browsed via the link-out function. ProBioQuest is not only useful to scientists and health professionals but also to dietary supplement manufacturers and the general public. In this paper, the method we used to build this database-web system is described. Applications of ProBioQuest for several literature-based analyses of probiotics are included as examples of the various uses of this search engine. ProBioQuest can be accessed free of charge at http://kwanlab.bio.cuhk.edu.hk/PBQ/ . Database URL: http://kwanlab.bio.cuhk.edu.hk/PBQ/